2013
DOI: 10.5194/hess-17-1635-2013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-variable evaluation of hydrological model predictions for a headwater basin in the Canadian Rocky Mountains

Abstract: Abstract.One of the purposes of the Cold Regions Hydrological Modelling platform (CRHM) is to diagnose inadequacies in the understanding of the hydrological cycle and its simulation. A physically based hydrological model including a full suite of snow and cold regions hydrology processes as well as warm season, hillslope and groundwater hydrology was developed in CRHM for application in the Marmot Creek Research Basin (∼ 9.4 km 2 ), located in the Front Ranges of the Canadian Rocky Mountains. Parameters were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
153
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 83 publications
1
153
0
Order By: Relevance
“…The mountains range in elevation from 1600 to 2800 m, and typical mountain environments include montane and subalpine forest cover, alpine tundra, and talus/rock at higher elevation. The climate is characterized by cool, wet summers and long, cold winters; monthly mean air temperature ranges from −10.7 • C in January to 11.7 • C in July (Pomeroy et al, 2012;Fang et al, 2013;Harder et al, 2015). There is a significant difference in the annual precipitation from 638 mm at the valley bottom to 1100 mm at higher elevations (Storr, 1967).…”
Section: Sites and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The mountains range in elevation from 1600 to 2800 m, and typical mountain environments include montane and subalpine forest cover, alpine tundra, and talus/rock at higher elevation. The climate is characterized by cool, wet summers and long, cold winters; monthly mean air temperature ranges from −10.7 • C in January to 11.7 • C in July (Pomeroy et al, 2012;Fang et al, 2013;Harder et al, 2015). There is a significant difference in the annual precipitation from 638 mm at the valley bottom to 1100 mm at higher elevations (Storr, 1967).…”
Section: Sites and Datamentioning
confidence: 99%
“…Depending on site characteristics and environment, gauge performance can vary widely. Results from numerous studies show that gauge type and collection method significantly affect measurement precision and accuracy (Emerson and Macek-Rowland, 1990;Yang et al, 1999). Although all precipitation measurements are prone to bias, the measurement biases are most serious in cold regions due to high snowfall percentage Yang et al, 1998Yang et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…The Cold Regions Hydrological Model (CRHM) was developed using these and other studies in Marmot Creek and used to describe the hydrology of the basin using physically based calculations of blowing and intercepted snow, snow sublimation, melt, infiltration into frozen soils, evaporation and soil physics representations Fang et al 2013). Perturbations of the model showed that forest disturbance impacts on snowpack were much greater than on streamflow because of the desynchronization of melt caused by forest removal in Marmot Creek .…”
Section: Research Studies 2004-2013mentioning
confidence: 99%
“…However, pine beetle kill of lodgepole pine had an insignificant impact on streamflow because it occurs at low elevations where precipitation is low and runoff generation is small. The most recent hydrological model can simulate the snowpack, soil moisture, groundwater and streamflow in Marmot Creek without calibration of parameters due to its reliance on the large number of scientific findings in the basin over 50 years (Fang et al 2013).…”
Section: Research Studies 2004-2013mentioning
confidence: 99%
“…The Marmot Creek catchment is currently instrumented with several permanent meteorological stations at different elevations, groundwater wells and stream gauges. Research focuses on mountain snow processes (snow accumulation and snowmelt), hydro-climatic trends and hydrological modelling (Pomeroy et al, 2012;Fang et al, 2013). Research projects in the Wolf Creek catchment (Yukon, Canada) were initiated in 1992 and include studies on water balance, hillslope runoff processes and runoff generation in permafrost areas by means of environmental tracers (Carey and Woo, 2001;Carey and Quinton, 2005).…”
Section: Introductionmentioning
confidence: 99%